The developing brain structural and functional connectome fingerprint. (June 2022) - Ciarrusta, Judit; Christiaens, Daan; Fitzgibbon, Sean P.; Dimitrova, Ralica; Hutter, Jana; Hughes, Emer; Duff, Eugene; Price, Anthony N.; Cordero-Grande, Lucilio; Tournier, J.-Donald; Rueckert, Daniel; Hajnal, Joseph V.; et al.
Abstract: In the mature brain, structural and functional 'fingerprints' of brain connectivity can be used to identify the uniqueness of an individual. However, whether the characteristics that make a given brain distinguishable from others already exist at birth remains unknown. Here, we used neuroimaging data from the developing Human Connectome Project (dHCP) of preterm born neonates who were scanned twice during the perinatal period to assess the developing brain fingerprint. We found that 62% of the participants could be identified based on the congruence of the later structural connectome to the initial connectivity matrix derived from the earlier timepoint. In contrast, similarity between functional connectomes of the same subject at different time points was low. Only 10% of the participants showed greater self-similarity in comparison to self-to-other-similarity for the functional connectome. These results suggest that structural connectivity is more stable in early life and can represent a potential connectome fingerprint of the individual: a relatively stable structural connectome appears to support a changing functional connectome at a time when neonates must rapidly acquire new skills to adapt to their new environment. Graphical Abstract: ga1 Highlights: The brain structural connectome can be used to identify an individual at birth Functional connectivity is less stable and cannot be used as a fingerprint Age at first scan and days between scans impacts on similarity Structural and functional similarity appear closest in central sulcus Age at first scan significantly impacts on parietal functional similarity